Pertussis-associated pneumonia in infants and children from low- and middle-income countries participating in the PERCH study - Barger-Kamate, B; Knoll, M; Kagucia, EW; Prosperi, C; Baggett, HC; Brooks, WA; Feikin, DR; Hammitt, LL; Howie, SRC; Levine, OS; Madhi, SA; Scott, JAG; et al. (Oxford University Press, 2016)
Background. Few data exist describing pertussis epidemiology among infants and children in low-and middle-income countries to guide preventive strategies. Methods. Children 1-59 months of age hospitalized withWorld Health Organization-defined severe or very severe pneumonia in 7 African and Asian countries and similarly aged community controls were enrolled in the Pneumonia Etiology Research for Child Health study. They underwent a standardized clinical evaluation and provided nasopharyngeal and oropharyngeal swabs and induced sputum (cases only) for Bordetella pertussis polymerase chain reaction. Risk factors and pertussis-associated clinical findings were identified. Results. Bordetella pertussis was detected in 53 of 4200 (1.3%) cases and 11 of 5196 (0.2%) controls. In the age stratum1-5months, 40 (2.3% of 1721) cases were positive, all from African sites, as were 8 (0.5% of 1617) controls. Pertussis-positive African cases 1-5 months old, compared to controls, were more often human immunodeficiency virus (HIV) uninfected-exposed (adjusted odds ratio [aOR], 2.2), unvaccinated (aOR, 3.7), underweight (aOR, 6.3), and too young to be immunized (aOR, 16.1) (all P ? .05). Compared with pertussisnegative African cases in this age group, pertussis-positive cases were younger, more likely to vomit (aOR, 2.6), to cough ?14 days (aOR, 6.3), to have leukocyte counts > 20 000 cells/?L (aOR, 4.6), and to have lymphocyte counts > 10 000 cells/?L (aOR, 7.2) (all P ? .05). The case fatality ratio of pertussis-infected pneumonia cases 1-5 months of age was 12.5% (95% confidence interval, 4.2%-26.8%; 5/40); pertussis was identified in 3.7% of 137 in-hospital deaths among African cases in this age group. Conclusions. In the postneonatal period, pertussis causes a small fraction of hospitalized pneumonia cases and deaths; however, case fatality is substantial. The propensity to infect unvaccinated infants and those at risk for insufficient immunity (too young to be vaccinated, premature, HIV-infected/exposed) suggests that the role for maternal vaccination should be considered along with efforts to reduce exposure to risk factors and to optimize childhood pertussis vaccination coverage.